Consider the following pair of equations:

y = 3x + 3
y = x − 1

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

Respuesta :

So the equations are: 

y= 3x + 3

y= x- 1

By the transitive property, we know x-1= 3x+3 (Transitive property means if a= b, and b= c, shouldn't a = c if they both equal b?)

so, x- 1= 3x + 3.  Now we isolate x and solve:
        +1          +1
x= 3x+ 4
-x  -x

0 = 2x+ 4
-4        -4

-4 = 2x
/2    /2

x= -2

Now, you can plug that back in to find y:

y = x- 1
y= -2 -1
y= -3

Then plug them both in to make sure it is correct. :o)
ACCESS MORE